Scalable MoS2/graphene hetero-structures grown epitaxially on sapphire substrates for phototransistor applications. (16th January 2018) - Chen, Hsuan-An; Chen, Wei-Chan; Sun, Hsu; Lin, Chien-Chung; Lin, Shih-Yen
Abstract: Bi-layer graphene is grown directly on sapphire substrates by using ethane as the precursor without the assistance of a metal catalyst. A growth model of graphene flake formation in the furnace, followed by a complete film growth is also proposed. Using the graphene/sapphire sample as the new substrate, scalable MoS2 films with good layer number controllability can be grown directly on the substrate. After fabricating the MoS2 /graphene hetero-structures into bottom-gate photo-transistors, a Dirac point shift is observed for the device under the light irradiation condition, which is attributed to the extraction of photo-excited electrons in the MoS2 layer to the graphene channel. The photo-voltaic response observed for the photo-transistors may provide a potential application of the 2D material hetero-structure in thin-film solar cells.